The Effect of Computer Based Game on Improving Nursing Students' Basic Life Support Application Skills: Experimental Study. - DEMİRAY, Ayşe; KESKİN KIZILTEPE, Selin (Turkiye Klinikleri Journal of Nursing Sciences, 2022)
Objective: The use of computer-aided simulation in the development of nursing students' basic life support skills has become increasingly widespread. The aim of this study is to evaluate the effect of computer-aided game in the development of basic life support application skills of second-year nursing students. Material and Methods: The universe of this randomised controlled study included 194 second-year nursing students of Health Sciences University who were enrolled in a first-aid lesson. Experimental and control groups were randomly selected among these students according to the results of power analysis. Experimental (n=28) and control (n=28) groups of the study were determined within the scope of simple random sampling method. The data were collected by using "Introductory Information Form", "Basic Life Support Skill Evaluation Form" which were prepared by the researchers. Quantitative data were presented as median (minimum-maximum), frequency (percent). Mann-Whitney U test was used for comparison of non-normally distributed paired groups. Statistical significance level was set at p <0.05. Results: In the study, no difference was found between the experimental and control groups regarding the basic life support application times and scores (p>0.05). However, it was determined that the performance of the students who used computer based game was better than those who did not. Conclusion: It is recommended that computer-aided 3D serious games should be developed and used in the education of nursing students and that studies on this subject should be increased.